Chinese Culture in “The Kitchen God's Wife” by Amy Tan - Rakhmonova Saodat Akmal kizi (Genius Journals, 2022)
Culture is a floorboard for knowledge, belief, art, moral, law, and habits. According to the Baidu definition of culture, “culture” refers to the cumulative deposit of knowledge, experience, beliefs, values, attitudes, meanings, hierarchies, religion, notions of time, roles, spatial relations, concepts of the universe, and material objects and possessions acquired by a group of people in the course of generations through individual and group striving. To be more exactly: Culture is the systems of knowledge shared by a relatively large group of people.
Keywords: Bao-bao; patriotic; kind; faithful